Transforming Gender Equality and Inclusion Within Higher Education in Ireland: Contemporary Perspectives (Palgrave Studies in Gender and Education; Education; Education (R0), 2025)
This open access book thematically reflects on and analyses the nature of change and transformation with respect to gender equality, inclusion and diversity across higher education in Ireland, from the perspectives of those who are pioneering change. The authors propose that power, gender dynamics and social relations can be challenged and altered through collective action, transforming the national policy framework, establishing a comprehensive evidence base, adopting new policy and approaches to promote equality in practice. They outline significant advances made in a 10 year period in terms of overcoming inequalities, structural challenges promoting inclusion and advancing diversity. This is achieved by consolidating the activities related to gender review processes and practices, higher education policy, policy enactment at the local level and lessons learned from national policy, strategy, and funding models. The chapters in this volume, presented under four thematic headings, showcase pioneering practice to a national and international audience and represent a contemporary opportunity to reflect on the nature of change within the context of higher education in Ireland. The book will be of interest to academics working in higher education, EDI, gender studies, disability studies and social justice in education, as well as higher education leadership, policymakers and EDI practitioners.